2019
DOI: 10.1111/cei.13362
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of regulatory B and T cells in helminth parasite-induced protection against allergic airway inflammation

Abstract: The prevalence of allergic asthma and incidences of helminth infections in humans are inversely correlated. Although experimental studies have established the causal relation between parasite infection and allergic asthma, the mechanism of the parasite-associated immunomodulation is not fully elucidated. Using a murine model of asthma and nematode parasite Heligmosomoides polygyrus, we investigated the roles of regulatory B cells (B reg ) and T cells (T reg ) in mediation of the protection against allergic ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Several parasitic molecules have been implicated in modulating the immune and allergic response of helminth-infected hosts [ 27 ]. It has been described that parasite infections can develop a strong response and high levels of IgE in allergic sufferers, i.e., asthma or tropical pulmonary eosinophilia [ 28 , 29 , 30 , 31 ]. Moreover, it seems that infections by A. lumbricoides, T. canis, T. trichiura , hookworm, and S. mansoni can cause allergic reactions in humans [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several parasitic molecules have been implicated in modulating the immune and allergic response of helminth-infected hosts [ 27 ]. It has been described that parasite infections can develop a strong response and high levels of IgE in allergic sufferers, i.e., asthma or tropical pulmonary eosinophilia [ 28 , 29 , 30 , 31 ]. Moreover, it seems that infections by A. lumbricoides, T. canis, T. trichiura , hookworm, and S. mansoni can cause allergic reactions in humans [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, from a clinical perspective, molecules that drive expansion, mobilization, or increased mucosal homing of 9Tregs are the holy grail for many disorders that result from immune dysregulation [57,58], and we will provide defined examples later in this review. Regulatory B cells (Bregs) are also a feature of helminth infections [59] and are the primary source of IL-10 and other tissue-protective proteins, including (Resistin-like molecule-α) RELMα [60,61]. Indeed, in mice infected with H. polygyrus, IL-10 + Breg cells were able to promote expansion and maintenance of IL-10 + FOXP3 + Treg cell populations [61].…”
Section: Helminths Induce Treg Activitymentioning
confidence: 99%
“…Regulatory B cells (Bregs) are also a feature of helminth infections [59] and are the primary source of IL-10 and other tissue-protective proteins, including (Resistin-like molecule-α) RELMα [60,61]. Indeed, in mice infected with H. polygyrus, IL-10 + Breg cells were able to promote expansion and maintenance of IL-10 + FOXP3 + Treg cell populations [61]. Fig 3 summarizes the multitude of cellular immune pathways upon which helminths and their ESPs impact, including the well-established influence of DCs, but also the emerging potential roles for factors produced by microbes, sensory neurons, and specialized intestinal epithelial cells that initiate the very early response to helminth exposure via ILC2s and innate granulocytes [62,63].…”
Section: Helminths Induce Treg Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cell transfer and depletion experiments demonstrated that IL-10 + Breg, IL-10 + Treg and FoxP3 + Treg cells participated in the parasite-induced immunosuppression of allergic airway inflammation. 99 …”
Section: Environmental Factors and Immunological Regulation Of Asthmamentioning
confidence: 99%